Incidence of the anterior resection syndrome using low anterior resection score (LARS scale) - Dulskas, Audrius; Smolskas, Edgaras; Kilius, Alfredas; Čižauskaitė, Agnė; Samalavičius, Narimantas Evaldas (Lietuvos chirurgija, 2017)
Background  Up to 90 % of patients undergoing low anterior resection, complain of increased daily bowel movements, urgency for defecation, and a variable degree of incontinence. A symptom-based scoring system for bowel dysfunction after low anterior resection for rectal cancer has recently been validated in Lithuanian population.  Purpose: we aimed to measure the incidence and severity of the anterior resection syndrome (ARS) using LARS and its correlation with selected variables or risk factors.Methods  LARS score was sent to 183 patients who underwent low anterior resection with TME with coloanal anastomosis from January 1st, 2008 to December 31st, 2012 at the National Cancer Institute. Of them 111 (responsibility was 60.7%) have completed the questionnaire. The variables studied were age, sex, location of the tumour, neoadjuvant radiotherapy, time after treatment.Results  Of 111 questionnaires 108 were completed properly (59.0%). 27 patients (25%) had no ARS, 26 (24%) had minor ARS and 55 (56%) had major ARS. In univariate analysis age, sex, neoadjuvant radiotherapy, and tumour localization did not have an im pact on severity of bowel dysfunction symptoms after low anterior resection with TME. Also there was no difference between female and male patient groups (p=0.33), patients who had/had not undergone radiation therapy (p=0.07), and those with low or high tumour edge level (p=0.17). However, time after operation (< 12 months) was associated to ARS.Conclusion  More than half of the operated patients presented severe LARS score and only a one fourth did not provide a quantifiable ARS. Timing after surgery was the main factor affecting ARS.
Keywords: low anterior resection; low anterior resection syndrome; LARS score; total mesorectal excision